Bilateral simple bone cyst in mandible: Rare case report - Marques,Milena Vargas (2021)
Abstract The simple bone cyst is a benign osteolytic lesion, uncommon in the maxillomandibular region. Its etiology remains unknown, although traumatic injuries are often associated with this injury. Young patients, men and women alike are the most affected. It is asymptomatic in most cases, being diagnosed on routine radiographs. The radiolucent image, uni or multilocular, is well defined, with irregular margins, mainly in the posterior region of the mandible. Bilateral presentation is unusual. The final diagnosis is made during surgical procedures when an empty bone cavity is detected. Simple curettage is the treatment of choice and it consists of causing bleeding and filling the cavity with a blood clot. Bone repair will be observed in the follow-up procedures. The aim of this study was to present a rare case of bilateral simple bone cyst in a young male, treated with curettage of the bone walls.